Implikasi Yuridis Undang-Undang Nomor 3 Tahun 2024 terhadap Kewenangan Badan Pemeriksa Keuangan (BPK) dalam Pemeriksaan Keuangan Desa - Yunus, Rahmawati; Abdussamad, Zamroni; Mandjo, Julius T (Adagium: Jurnal Ilmiah Hukum, 2025)
The study aims to examine the legal implications of Law No. 3 of 2024 on the authority of the Supreme Audit Agency (BPK) in conducting financial audits of villages. The main issue raised is how these regulatory changes expand, clarify, and strengthen the role of the BPK in directly overseeing village financial management, as well as their impact on transparency, accountability, and financial governance in villages. The research approach applied is a legal study from the perspectives of legislation, history, comparison, and conceptual analysis. Information was collected through literature review using official regulations, official documents, legal literature, and relevant previous study findings. The study findings show that Law No. 3 of 2024 provides a stronger legal basis for the BPK to conduct direct audits of villages, no longer limited to audits of district/city budgets. The BPK's authority now includes administrative audits, performance audits, and investigative audits, making village financial oversight more comprehensive and substantive. The impact of these changes is increased transparency, accountability, and public participation in village financial oversight, as well as the strengthening of good governance principles at the village level. This study underscores the importance of strengthening village government capacity, inter-agency collaboration, and the development of open reporting systems to support the effectiveness of village financial oversight in the new regulatory era.